A survey of scale insects (Hemiptera: Coccoidea) in citrus orchards in São Paulo, Brazil - Almeida, Luís Fernando V. [UNESP]; Peronti, Ana Lúcia B. G. [UNESP]; Martinelli, Nilza Maria [UNESP]; Wolff, Vera R. S. (De Gruyter, 2018)
Many scale insects (Hemiptera: Coccoidea), including species of great economic importance, are associated with plants of the genus Citrus in citrusproducing regions around the world. Revision and updating of lists of scale insect species based on field surveys contributes to improving their management and is an important tool for preventing their introduction into non-infested areas. The purpose of this study was to present an updated list of scale insect species in citrus orchards in São Paulo, Brazil. Samples were collected between Sep 2014 and Sep 2015, and between Sep 2016 and Jul 2017, from rural and urban areas and from nurseries in 27 municipalities in the principal citrus-producing regions in the state of São Paulo, known as the citrus belt. A total of 22 species in 6 families were identified: (1) Coccidae: Ceroplastes floridensis Comstock, Coccus viridis (Green), Parasaissetia nigra (Nietner), Saissetia coffeae (Walker); (2) Diaspididae: Acutaspis scutiformis (Cockerell), Aonidiella aurantii (Maskell), Chrysomphalus aonidum (L.), Lepidosaphes gloverii (Packard), Melanaspis smilacis (Comstock), Parlatoria cinerea Hadden in Doane & Hadden, Parlatoria ziziphi (Lucas), Pinnaspis aspidistrae (Signoret), Pseudaonidia trilobitiformis (Green), Selenaspidus articulatus (Morgan), Unaspis citri (Comstock); (3) Lecanodiaspididae: Lecanodiaspis rugosa Hempel; (4) Monophlebidae: Icerya purchasi Maskell; (5) Ortheziidae: Praelongorthezia praelonga (Douglas), and (6) Pseudococcidae: Ferrisia virgata (Cockerell), Leptococcus minutus (Hempel), Planococcus citri (Risso), and Pseudococcus cryptus Hempel. This is the first report of L. gloverii, P. nigra, P. aspidistrae, P. trilobitiformis, and P. cryptus on citrus in São Paulo, and of M. smilacis on Rutaceae host plants. Parlatoria ziziphi, S. articulatus, and U. citri were the most frequently observed species on the sampled plants, and they are among those that reached high levels of infestation throughout the collection period. A review of all scale insects associated with Citrus spp. in Brazil also is included.
Keywords: Citriculture; Coccidae; Diaspididae; Monophlebidae; Ortheziidae; Pseudococcidae; South America